MAKNA, TINGKATAN, DAN IMPLEMENTASI SYUKUR DALAM TAFSIR SUFISTIK: STUDI ATAS Q.S. IBRAHIM AYAT 7 MENURUT ABDUL QADIR AL-JILANI - Siregar, Muhammad Sururi Alfajri Wannahar; Linda Suanti; Zulfi Akmal; Hendra Syafrianto; Dame Siregar (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study discusses the interpretation of Surah Ibrahim verse 7 by Abdul Qadir al-Jilani in Tafsir al-Jilani, focusing on the meaning, levels, and implementation of gratitude (syukr) in a Sufi perspective. Using a qualitative method with a library study approach, this study analyzes primary sources and contextual literature to reveal the structure of al-Jilani's interpretation. The results of the study indicate that gratitude is not only understood as a moral obligation, but also as a process of spiritual ascent consisting of five levels: hidayah (guidance), khidmah (devotion), musyahadah (witnessing), walayah (closeness), and ru'yah (spiritual vision towards God). Gratitude is positioned as a transcendental consciousness that forms a deep relationship between servants and Allah. This study concludes that the Sufi interpretation of gratitude in this verse provides a valuable spiritual model in understanding the integration between ethics, worship, and spiritual awareness. These findings can enrich the discourse of interpretation, Islamic ethics, and the development of psychology and spiritual education in the contemporary context.